Accident investigation challenges for process safety practitioners. Issue 4 (19th April 2019) - Selk, Stephen; Benner, Ludwig
Abstract : Investigations related to the process industry may be conducted for many kinds of unexpected occurrences including unintentional as well as intentional, relatively uncomplicated or very complex, with minor, serious or catastrophic consequences. Personnel in the process industries may become involved in any such kinds of investigations. Before getting involved, they should be aware of what will be expected of them, and how to prepare for and respond appropriately to those expectations. This report provides some information about those expectations and their origins, issues personnel are likely to encounter, and suggestions for coping with them. © 2019 American Institute of Chemical Engineers Process Saf Prog: e12053 2019